MAKING PAPER FROM MIXTURE OF OIL PALM FRONDS (OPF) AND OIL PALM EMPTY FRUIT BUNCHES (OPEFB) - Nanna Nanna; Syahrul Rhamadhani; Siti Aminah; Aji Larasati Putri Riadi; Novy Pralisa Putri (Konversi, 2020)
The oil palm industry produces solid waste such as oil palm fronds (OPF) and empty fruit bunches (OPEFB), but the utilization of the OPEFB waste is still limited to composting. Even the palm fronds are only left on the farm without being processed. While both types of waste contain a lot of cellulose and can be processed into more economic value. In addition to compost, the two types of waste can be used as pulp and paper. Hence, in this study, the two wastes are processed into the paper with a variety of concentrations of solvents and mixtures. The aim is to determine the effect of solvent concentration in the process of making paper pulp and the effect of the comparison of the mixture of paper pulp with the characteristics of the paper produced. Each material is processed into pulp by the soda process using sodium hydroxide as a solvent. While the solvent concentration used is 20%, 30%, and 40% for materials from OPEFB, while the material from OPF is only mixed with 20% sodium hydroxide solution. Then the pulp, OPEFB pulp with various variations of solvent, mixed pulp with the ratio of OPF pulp and OPEFB pulp of 1: 3; 1: 1; and 3: 1 processed into paper. The resulting paper was analyzed to study folding strength, tear strength, and paper thickness. The results of the study prove that the folding endurance and tear resistance of the paper have smaller in the greater concentration of the solvent. By contrast, the thickness of the paper is greater. Besides, more the mass of OPEFB in the pulp mixture, then the folding endurance and tear resistance of the paper have less, while the thickness is decreasing.